Negative Corporate Disclosure and Stock Price Decline: A Normative Legal Analysis of Investor Protection in Indonesia’s Capital Market - Amar Ma'ruf; Arvian Wiyanggoro (Journal of Private and Commercial Law, 2024)
This study examines the impact of negative corporate disclosure on stock price movements and investor protection in Indonesia’s capital market. The primary objective is to analyze how negative information disseminated through the Indonesia Stock Exchange (IDX) affects investor behavior and market performance. Using a normative legal research approach, this study relies on library-based data collection and employs both statutory and conceptual analyses. The case of PT X, a publicly listed company, and its subsidiary PT Y, an eSAF frame manufacturer for motor vehicles, serves as an illustrative example. The findings demonstrate that negative publicity—particularly related to product concerns such as weight and corrosion resistance—can significantly influence investor perception, even when the product is generally considered to have good quality. The circulation of adverse information triggers investor panic and leads to widespread share sell-offs, ultimately resulting in a decline in PT X’s stock price. This confirms that stock prices tend to move rapidly in response to negative news, reflecting the sensitivity of market behavior to reputational risk and information flow. From a legal perspective, these dynamics raise important questions regarding the adequacy of disclosure obligations and investor protection mechanisms within Indonesia’s regulatory framework. This research contributes by bridging capital market law and investor behavior, highlighting the relationship between corporate news, investor decision-making, and stock market activity. It underscores the need for stronger transparency standards and more effective legal safeguards to mitigate the impact of negative disclosures, offering practical insights for regulators, corporations, and investors in emerging markets.